Border museum as pedagogical space: Strengthening students' nationalism through contextualized history learning in Anambas - Simanjuntak, Adelina Darmauli; Rochmat, Saefur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Border museums have the potential to serve as contextualized educational spaces that foster students’ nationalism, particularly in geographically isolated and culturally complex frontier regions. This study investigates how border museums are integrated into history education and how they contribute to students’ national identity development in the Anambas Islands, a peripheral maritime region of Indonesia. Employing a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis across two public high schools and the Anambas Border Museum. A purposive sampling technique was used to recruit participants, including 40 students, 4 history teachers, and 6 stakeholders such as museum managers, principals, and community leaders. The findings reveal that museum-based history learning enhances students’ engagement with local historical narratives, cultivates pride in national identity, and promotes experiential and reflective learning. Teachers act as key mediators in contextualizing museum content, while institutional challenges such as limited infrastructure and weak curriculum integration hinder full implementation. The study provides practical insights for developing pedagogical models that leverage local cultural institutions to promote nationalism and civic awareness in marginalized border areas. These findings contribute to education policy discourse, particularly regarding the integration of cultural heritage institutions into formal history curricula in remote and underserved contexts.